Can serum 8-hydroxy-2'-deoxyguanosine levels reflect the severity of pulmonary arterial hypertension? - Coskun,Fatma Yılmaz (2021)
SUMMARY OBJECTIVE: Oxidative stress plays a pivotal role in the pathogenesis of pulmonary arterial hypertension. 8-Hydroxy-2'-deoxyguanosine is a sensitive biomarker that reflects the degree of oxidative damage to DNA. We investigated whether serum 8-Hydroxy-2'-deoxyguanosine is a clinically useful biomarker for the severity of pulmonary arterial hypertension. METHODS: We measured serum 8-Hydroxy-2'-deoxyguanosine levels in 25 patients (age 37±13 years, 68% women) diagnosed with idiopathic pulmonary arterial hypertension, familial pulmonary arterial hypertension, or pulmonary arterial hypertension associated with congenital heart disease. The severity of pulmonary arterial hypertension was evaluated by six-min walking distance, World Health Organization functional class, and serum brain natriuretic peptide levels. Age and gender-matched 22 healthy subjects served as the control group. RESULTS: The comparison of 8-Hydroxy-2'-deoxyguanosine levels between patients and controls was not statistically different [(19.86±9.79) versus (18.80±3.94) ng/mL, p=0.622)]. However, there was a significant negative correlation between 8-Hydroxy-2'-deoxyguanosine levels and six-min walking distance (r= −0.614, p=0.001). Additionally, serum 8-Hydroxy-2'-deoxyguanosine levels in patients with functional class III–IV were significantly higher than those with functional class I–II (functional class III–IV 32.31±10.63 ng/mL versus functional class I–II 16.74±6.81 ng/mL, respectively, p=0.003). CONCLUSION: The 8-Hydroxy-2'-deoxyguanosine levels were significantly correlated with exercise capacity (six-min walking distance) and symptomatic status (functional class), both of which show the severity of pulmonary arterial hypertension in patients.